Teachers' narratives of Fort McMurray - Harper, Brian; University of Lethbridge. Faculty of Education (Lethbridge, Alta. : University of Lethbridge, Faculty of Education, 2004, 2004)
vii, 46 leaves 29 cm. -- The purpose of this project was to share the stories offive teachers who have taught in Fort McMurray. The study began with the digital recording of images and sounds in the community that were linked with video clips of the interviews conducted with teachers. Such an audio-visual collage provided an added perspective to the narrative ofteaching and living in Fort McMurray. Fort McMurray, in Northern Alberta, is a unique place to live. Geographically and socially it has a physical landscape that can be overwhelming to some while others find it supports a dynamic human landscape. Depending upon one's perspective this community rests at either end ofthe desirability scale of places to live and teach. When I arrived, I was one the youngest teachers in my school. Elder mentors have begun to retire and people my age are taking more leadership roles. In many communities, it takes decades to outgrow the newcomer appellation. But, in Fort McMurray the ideas of cooperation and belonging seem to be enhanced. These ideas and their corollaries, distance and isolation, were explored with five teachers who have lived in Fort McMurray between 15 and 30 years. Interview excerpts and literature on teachers' narratives, ethnography, and learning communities have helped to make connections and deepen my understanding of belonging in this particular place. Travelling from Fort McMurray to attain a Master of Education degree at the University of Lethbridge was a personally challenging and professionally rewarding experience. I was comforted by the simplicity of a stark prairie landscape while studying at Lethbridge and appreciative of the Internet environment provided by the faculty for working at home, 1000 kilometres north. However, as deeply as I was enriched by those experiences, readings, seminars, writing, research, institutes, and online discussions, none of it would matter without a place to teach. The desire to create an electronic representation ofthe teachers' stories arose from my interests ...